Synopsis: Study of the determinants of chronic malnutrition in northern Nigeria: Qualitative evidence from Kebbi and Bauchi states - Benson, Todd; Amare, Mulubrhan; Oyeyemi, Motunrayo; Fadare, Olusegun (International Food Policy Research Institute, 2017)
To inform discussions on future programming to improve child nutrition, a rapid scoping study of the drivers of undernutrition in northern Nigeria was conducted. This report presents insights obtained from almost 70 key informants interviews and focus group discussions conducted in April and May 2017 in Kebbi and Bauchi states and in Abuja (Figure 1). The participants in these interviews and discussions included mothers and fathers of young children, community civic and religious leaders, local medical and public health officers, state-level officials from government and non-governmental organizations (NGO), experts on human nutrition, and national-level government and NGO officials.